The intellectual significance of the sign in the visual text (caricature art)as a model (Journal of the College of Basic Education, 2024)
The research addressed the situation (the intellectual significance of the sign in the caricature visual text) through four chapters it including .The first chapter is devoted to explaining the research problem and its importance ,the research objective and its limits , and defining the most important terms contained therein . This study sought to provide a theoretical introduction and a coordinated analysis of the visual text of the caricature in light of the semiotics of the sign and its intellectual connotation in order to try to understand the viewer through the language of the image and its intellectual semantic value and to know its truth and the strength of its impact on the recipient , including the symbols and semantic implications it carries ,whether political ,social ,or cultural, in multiple procedural steps .The study adopted the descriptive approach , to analyze the intellectual and symbolic content of the sign and its various visual formulations ,revealing that it possesses the necessary keys to the interpretive process ,and the results that ; The caricatured image is a visual reality full of intertextuality that contributes to arousing the recipient’s aesthetic feeling ,Take up the second chapter; dealt with the structure of the sign and its types, the concept of the image , the perceptual structure ,the caricature ,its types and functions ,and the chapter ends with indicators of the theoretical framework .and the third chapter was concerned with research procedures ,including the research population and testing the sample of (5) works. While the fourth chapter included the results , conclusions, recommendations and proposals .